MEMBANGUN JIWA KEWIRAUSAHAAN UNTUK MEWUJUDKAN NILAI EKONOMI YANG SEJAHTERA DI PADUKUHAN SRUMBUNG SEGOROYOSO, PLERET, BANTUL DAERAH ISTIMEWA YOGYAKARTA - Herman Wahyu Dwi Maelana; Yuliantoharinugroho Yuliantoharinugroho; Luluk Priyanti; Dedi Prayitno; Wahyudiyono Wahyudiyono; Irine Diana Sari Wijayanti (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2023)
The impact of the Covid-19 pandemic is still being felt by the community, especially people in rural areas. Even though the graph of Covid-19 sufferers has been sloping, the passion to increase enthusiasm to restore the family economy still requires support and encouragement. The purpose of this community service activity is to build the entrepreneurial spirit of the community in Srumbung, Pleret, Bantul DIY to improve the economy and welfare of the community, thereby increasing the independence of the Srumbung Village community. This community service activity was attended by the people of the Srumbung Village, especially the Farmers, Breeders and people who have home-made products. This activity involved a team of AMA Yogyakarta lecturers in an effort to build a spirit of entrepreneurship. As a result of this community service, it is hoped that the people of Srumbung Village will return to their enthusiasm and enthusiasm for starting a business and developing existing businesses.